2013
DOI: 10.1080/13607863.2012.715139
|View full text |Cite
|
Sign up to set email alerts
|

A narrative exploration of older people's transitions into residential care

Abstract: Professionals should move away from considering transition as a stage-based process ending in acceptance, instead focussing on how residents perceive relocation in relation to previous life experiences, unspoken fears evoked by moving and how the environment and relationships with staff may be altered to assist residents in maintaining their identity and sense of control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 40 publications
4
87
0
1
Order By: Relevance
“…There was wide variation in the degree to which participants with dementia had adjusted to their new environment at the time of the interviews, which on average occurred four months after their admission. Consistent with previous reports (Aminzadeh et al, ; Clare, Rowlands, Bruce, Surr, & Downs, ; Lee, Woo, & Mackenzie, ; Lee, Simpson, & Froggatt, ; Nay, ), residents with dementia in this study appeared to be, at best, resigned to their changed circumstances, rather than to have meaningfully “adjusted”. While some residents tried to make the most of a situation not of their choosing, others felt trapped and expressed a strong desire to leave.…”
Section: Discussionsupporting
confidence: 90%
“…There was wide variation in the degree to which participants with dementia had adjusted to their new environment at the time of the interviews, which on average occurred four months after their admission. Consistent with previous reports (Aminzadeh et al, ; Clare, Rowlands, Bruce, Surr, & Downs, ; Lee, Woo, & Mackenzie, ; Lee, Simpson, & Froggatt, ; Nay, ), residents with dementia in this study appeared to be, at best, resigned to their changed circumstances, rather than to have meaningfully “adjusted”. While some residents tried to make the most of a situation not of their choosing, others felt trapped and expressed a strong desire to leave.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, when it comes to establishing new relationships in the NH, our study implies that residents avoid contact with fellow residents because of their perceived fellows’ cognitive impairment. This is similar to a study of Lee, Simpson and Frogatt , highlighting the extent of older adults’ fear of losing their memory: participants in this study distanced themselves from other residents based on their abilities, specifically in relation to memory. With respect to group activities, events organised by the NH give residents the feeling of belonging to a group, which also seemed to reduce loneliness for some participants in our study .…”
Section: Discussionsupporting
confidence: 86%
“…Other studies have identified physical and mental health problems requiring care over a 24-hour period or supervision as reasons for care home admission (Bebbington et al, 2001;Lee et al, 2013). In this study participants experienced some difficulties with mobility requiring the use of a walking aid, but were not restricted in their ability to move around the care home, for example, one participant stated:…”
Section: Choosing the Pathmentioning
confidence: 80%